Implikasi Korupsi Pertamina Terhadap Kepercayaan Investor dan Pertumbuhan GDP Nasional - Aradea Margareta; Alfina Marta; Rara Marcela; Ratu Aribah Santika Xaviera (STIE Indonesia Banking School, 2025)
In the economic sector, corruption will certainly complicate economic development, which in the private sector will certainly increase costs due to illegal payments and the risk of canceling agreements or investigations. Corruption has a huge impact, including slowing down the country's economic growth and decreasing investment, creating income inequality, and increasing poverty in the country. This research aims to analyze the impact of corruption in Pertamina on Indonesia's economic stability, investor confidence, and Gross domestic product (GDP) growth. By using descriptive qualitative research methods to collect data from the Ministry of Finance related to fuel subsidies, as well as investment movements in the energy sector. The results showed that the corruption case at Pertamina had a negative impact on economic stability. In addition, investor confidence in Indonesia's energy sector has decreased, which is characterized by weakening foreign direct investment and fluctuations in the capital market. The broader impact was also seen in GDP growth, where the oil and gas sector, which was previously one of the main pillars of the economy, slowed down due to the instability caused by the corruption case. This study recommends increased transparency and better corporate governance through the implementation of Good corporate governance (GCG).